Documentation of Ethnoveterinary Practices for Mastitis in Dairy Animals in Pakistan - S. M. Raihan Dilshad, N. U. Rehman*, Nazir Ahmad and A. Iqbal1 (Pakistan Veterinary Journal, 2010)
This study was aimed to document the ethnoveterinary practices (EVPs) used for the control and treatment of mastitis in cattle and buffaloes in the Sargodha district, Pakistan. The information was collected using rapid and participatory rural appraisal techniques through interviews and focused group discussions with 217 traditional veterinary healers (TVHs) over a period of 16 months from September 2005 to December 2006. Thus, 25 different plant species belonging to 20 different families were documented from the study area for the treatment and prophylaxis of mastitis in bovines (cattle) and bubalines (dairy buffalo, Bubalus bubalis). The most frequently reported (≥10 times) plant species were Capsicum annuum L. (n = 32), Lepidium sativum L. (n =31), Allium sativum L. (n = 28), Sesamum indicum L. (n = 24), Citrus limon (L.) Burm. f (n = 22), Zingiber officinale Roscoe (n = 18), Citrullus colocynthis (L.) Schrad (n = 18), Curcuma longa L. (n = 16), Cuminum cyminum L. (n = 14), Rosa indica L. (n = 13), Centratherum anthelmisticum L. (n = 12), Triticum aestivum L (n = 11), Nigella sativa L. (n = 11) and Peganum harmala L. (n = 11). All the documented plant species were indigenous to the study area. Materials other than plants used for the treatment of this problem included ammonium chloride. The richness of EVPs in the study area and extensive variation in the doses, methods of preparation, indications, and claims regarding efficacy of plants for mastitis merit controlled studies for their validation.